(untitled) (Scientific journal of the Fergana State University, 2025)
For the first time, using the HPLC method and instrumental neutron activation analysis, the quantitative composition of 6 flavonoids and 38 macro- and microelements in the above-ground parts of Taraxacum officinale Wigg. s.L., growing in the territory of Fergana, was studied. It was established that dihydroquercetin (25.2 mg/g) predominates in the composition of Taraxacum officinale Wigg. s.L., along with macro- and microelements such as Na (920 mg/kg), Ca (38700 mg/kg), Fe (2970 mg/kg), Mn (94.5 mg/kg), and Cu (15 mg/kg). The amount of toxic elements in the plant does not exceed the maximum permissible concentration.